Coronary flow measurements in arterial grafts in reference to surgical technique - Maruszewski, Marcin; Hrapkowicz, Tomasz; Pacholewicz, Jerzy; Filipiak, Krzysztof; Nadziakiewicz, Paweł; Herdyńska-Wąs, Mirosława; Włoczka, Grzegorz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction: The application of coronary flow measurements has become either a standard or an abandoned procedure in cardiac surgery units. We have used Medistim Butterfly to assess coronary flow based on clinical indications in our centre since 2003. Objective : The primary objective of this analysis is to determine whether intraoperative coronary flow measurement is a useful tool that improves surgical outcome, patient care and safety. Material and methods : A retrospective analysis of a single centre’s two-year experience with coronary flow measurement was performed. Patients were divided into Group A (flow measurements performed) and Group B (measurements not performed). The results were analysed with respect to the operative technique, i.e. on-pump (CABG) and off-pump (OPCAB, MIDCAB), as well as all-arterial revascularization performed. Short-term outcomes (myocardial infarction, inotropic support, length of ICU and hospital stay, and mortality) were analysed. Statistical analysis was performed using Student’s t-test and Mann-Whitney U test (for numerical data), and chi-square test (for distribution analysis). Results: A total of 1748 coronary procedures (all procedures) were performed in our centre in 2007-8 (CABG: 1030 vs. OPCAB: 639 vs. MIDCAB: 79) including 253 all-arterial cases (58 vs. 131 vs. 79, respectively). The incidence of intraoperative myocardial infarction was significantly higher in Group A as well as postoperative use of IABP. The postoperative use of inotropes was significantly lower in Group A. Overall ICU stay was significantly longer in Group A. There was no difference in mean length of hospital stay or hospital mortality between the groups. Conclusions : Clinical indications for intraoperative coronary flow measurement may include poor contrast runoff during angiography, small coronary diameter, disseminated atherosclerosis, technical difficulties and patient unstable haemodynamic status. Determination of poor coronary flow allows for prevention of further haemodynamic instability with the use of IABP and extension of ICU stay. The immediate notice of inadequate revascularization may result in different patient monitoring and care allowing for safe hospital treatment and discharge.